BENARKAH DESENTRALISASI MENINGKATKAN PELAYANAN PUBLIK? (STUDI PERSEPSI PERUSAHAAN KEHUTANAN TERHADAP PELAYANAN PEMERINTAH SEBELUM DAN SETELAH DESENTRALISASI) - Sulistya Ekawati,M.Sc (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2017)
Decentralization is an important element in improving the country's ability to provide more effective and responsive services. Most of the production forest in Indonesia is managed by private sectors through forest concessions mechanism.The study aimed to analyze the perception of forest concession holders on government services. The research was conducted in Pelalawan District (Riau Province) and Kutai Timur District (East Kalimantan Province) by conducting interviews with key persons, and then the results were verified through focus group discussions with related stakeholders. The results showed that there were an increase of services in validating of the Business Work Plan (RKU) and Annual Work Plan (RKT) permits, technical supervision service (Wasganis) and letter of outstanding debt free of the Forest Resources Provision/Reforestation Fund (PSDH/DR) after decentralisation. While, monitoring and evaluation of RKT and corridor developement, generally better during the centralization period. Improvement of public services was not followed by the improvement of working environment and investment security for forest concessionaires.